(NsEJSMO\LEKTROMAGNITNYE QWLENIQ (B/s - (NgOHBERG(B, (NmIHAIL bORISOWI^s; (NmORGUNOW(B, (NwITALIJ aLEKSANDROWI^s; (NpOHOTELOW(B, (NoLEG aLEKSANDROWI^s; (NsADOWSKIJ(B, (Nm(B.(Na(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 161-170 (236 (NNAZW(B.)s
Keywords: (NzEMLETRQSENIQ (B- (NpROGNOZs